Obsessive-Compulsive Symptoms, Polygenic Risk Score, and Thalamic Development in Children From the Brazilian High-Risk Cohort for Mental Conditions (BHRCS) - Ravagnani Salto, Ana Beatriz; Santoro, Marcos L.; Hoexter, Marcelo Q.; Jackowski, Andrea Parolin; Pan, Pedro M.; Rosário, Maria Conceição; Belangero, Sintia I.; Alvarenga, Pedro Gomes; Doretto, Victoria Fogaça; Fumo, Afonso Mazine Tiago; Batistuzzo, Marcelo C.; Macul Ferreira de Barros, Pedro; et al. (Frontiers in Psychiatry, 2021)
Background: Thalamic volume measures have been linked to obsessive-compulsive disorder (OCD) in children and adolescents. However, it is unclear if alterations in thalamic volumes occur before or after symptom onset and if there is a relation to the presence of sub-clinical obsessive-compulsive symptoms (OCS). Here, we explore the relationship between OCS and the rate of thalamic volume change in a cohort of children and youth at high risk to develop a mental disorder. A secondary aim was to determine if there is a relationship between OCS and the individual's OCD polygenic risk score (OCD-PRS) and between the rate of thalamic volume change and the OCD-PRS. Methods: The sample included 378 children enrolled in the longitudinal Brazilian High-Risk Cohort for Mental Conditions. Participants were assessed for OCS and the symmetrized percent change (SPC) of thalamic volume across two time-points separated by 3 years, along with the OCD-PRS. Zero-altered negative binomial models were used to analyze the relationship between OCS and thalamic SPC. Multiple linear regressions were used to examine the relationship between thalamic SPC and OCD-PRS. Results: A significant relationship between OCS and the right thalamus SPC (p = 0.042) was found. There was no significant relationship between changes in thalamic volume SPC and OCD-PRS. Conclusions: The findings suggest that changes in the right thalamic volume over the course of 3 years in children may be associated to OCS. Future studies are needed to confirm these results and further characterize the specific nature of OCS symptoms associated with thalamic volumes.